2006
DOI: 10.1002/hep.21380
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cholesterol is hyperresponsive to statin in ABCG5/ABCG8 transgenic mice

Abstract: Interindividual variation exists in response to statin therapy. It has been hypothesized that subjects with higher baseline cholesterol synthesis rates are more sensitive to statins. To directly test this hypothesis, mice overexpressing the heterodimeric ATP-binding cassette (ABC) transporter G5/G8 (G5G8 Tg mice) were treated with lovastatin because they have a compensatory increase in cholesterol biosynthesis as a result of increased cholesterol excretion into bile and feces. As expected, lovastatin treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
1
21
1
Order By: Relevance
“…This fi nding is consistent with previous reports that pitavastatin increased the mRNA of Abca1 in rat hepatoma cell lines ( 31 ) and simvastatin promoted Abca1 expression in mice with atherogenesis ( 47 ). A synergistic hypocholesterolemic effect could be potentially achieved by simultaneously inhibiting cholesterol biosynthesis and promoting Abcg5/Abcg8-mediated cholesterol excretion ( 48 ). Therefore, enhanced cholesterol excretion is likely an additional mechanism for atorvastatin to lower cholesterol.…”
Section: Discussionsupporting
confidence: 92%
“…This fi nding is consistent with previous reports that pitavastatin increased the mRNA of Abca1 in rat hepatoma cell lines ( 31 ) and simvastatin promoted Abca1 expression in mice with atherogenesis ( 47 ). A synergistic hypocholesterolemic effect could be potentially achieved by simultaneously inhibiting cholesterol biosynthesis and promoting Abcg5/Abcg8-mediated cholesterol excretion ( 48 ). Therefore, enhanced cholesterol excretion is likely an additional mechanism for atorvastatin to lower cholesterol.…”
Section: Discussionsupporting
confidence: 92%
“…In animal models, hepatic expression of ABCG5/8 has been shown to be increased following statin therapy, which was associated with an increase in biliary cholesterol concentration ( 51,52 ). Lally et al ( 53 ) reported a signifi cant increase in intestinal ABGC5/8 mRNA expression in diabetic patients following treatment with statins.…”
Section: Discussionmentioning
confidence: 99%
“…The qPCR was performed as described previously ( 39 ). All primers used for qPCR have been published previously ( 39,40 ).…”
Section: Quantitative Real-time Pcr (Qpcr)mentioning
confidence: 99%